Noninvasive Imaging of Processes in Natural Porous Media: From Pore to Field Scale - Pohlmeier, A. (2020)
Noninvasive, high‐resolution imaging techniques are important for visualizing water flow and transport processes in soils, which are natural porous media. They are a key to understanding effects such as crop production, water resource restoration, CO2 sequestration, or the transport and fate of pollutants. During the last two decades, the development of three‐dimensional imaging techniques such as nuclear magnetic resonance imaging (NMR and MRI), X‐ray computed tomography (CT), and neutron CT has made significant progress possible in the study of soil processes. This special section presents examples of X‐ray CT and NMR from the small‐column scale to the application of portable NMR equipment in the field, along with some important advances in image processing that make it possible to extract optimal physical information from the original data.